Dynamics of Inflation and Manufacturing Sector Performance in Nigeria: Analysis of Effect and Causality - Judith, Modebe Nwanneka; Chijindu, Ezeaku Hillary (International Journal of Economics and Financial Issues, 2016)
The inflation-growth linkage has been on the front burner of academic discourses. However, the relations between inflation and growth have mostly been studied at an aggregate level and the need to relate inflation to some specific activity sectors of an economy rather than from the perspective of total growth have been largely ignored. This gap in knowledge motivated this study which is aimed at examining the linkage between inflation and manufacturing sector growth in Nigeria using annualized time series data from 1982 to 2014. The baseline regression results reveal that inflation and interest rate have negative and non-significant effect on manufacturing sector growth while exchange rate appear to positively and significantly influence the growth of manufacturing sector value added. Granger causality results reveal a unidirectional causality running from exchange rate to output growth. Inflation and interest rate however are not causal for output growth and vice versa. Keywords: Inflation, Manufacturing Sector, VECM. JEL Classifications: E02, E40